TREATMENT OF DISTAL URETERIC STONES-COMPARATIVE EFFICACY OF TRANSURETERAL PNEUMATIC LITHOTRIPSY AND EXTRACORPOREAL SHOCK WAVE LITHOTRIPSY - Wazir, Bakhtawar Gul; Orakzai, Akhtar Nawaz; Nawaz, Ahmad (Journal of Ayub Medical College Abbottabad, 2015)
Background: Ureteric stones greater than 6mm require intervention. Extracorporeal shockwave lithotripsy (ESWL) and ureteroscopy (URS) with intra-corporeal lithotripsy (ICL) are two least invasive therapies. Both show acceptable stone clearance. What should be the first line of treatment in distal ureteric stones? We conducted this study to compare the efficacy of ESWL and pneumatic ICL in order to develop clear cut treatment guidelines. Methods: This randomized control trial was conducted at Institute of Kidney Diseases, Peshawar from June 2011 to June 2012. Two hundred and twenty-four patients with distal ureteric stones 6-12 mm in size were included. Patients were randomized into two groups. Group-A patients were treated with URS plus ICL and Group-B with ESWL. Patients were evaluated for stone clearance after 2 weeks, with X-ray KUB and ultrasound. All the data were recorded in a pro forma and analysed in SPSS 10. Fisher’s exact test was applied to compare the efficacy and a p-value of 0.05 was considered significant. Results: Out of 112 patients in Group-A, 75 (67%) were males and 37 (33%) were females while in Group-B 79 (70.5%) were males and 33 (29.5%) were females. The mean age in Group-A was, 48.73±16.23 years whereas it was 46±14.58 years in Group-B. Overall, mean age was 47.36±15.4 years. Mean stone size was 9.18±1.6 mm. At follow up (2 weeks post-operative) URS with ICL was successful in 101 (90.2%) patients while ESWL was successful in 75 (67%) patients (p-value=0.0001). Conclusion: Extracorporeal shockwave lithotripsy shows acceptable stone clearance but ureteroscopy with intra-corporeal lithotripsy shows superior results in distal ureteric stones. Keywords: Pneumatic lithotripsy, ureteral calculi, ureteroscopy, extracorporeal shockwave lithotripsy